Removal of Fouling from Steel Plate Surfaces Based on Multi-Frequency Eco-Friendly Ultrasonic Guided Wave Technology - HUANG, Mingkun; JIN, Shuo; NIE, Gaoqian; WANG, Xiaopeng; ZHANG, Quanpeng; AN, Yang; QU, Zhigang; YIN, Wuliang (Archives of Acoustics, 2023)
Fouling is inevitable on the surfaces of industrial equipment, especially on heat-exchanging surfaces in contact with fluids, which causes water pollution and destroys the ecological environment. In this paper, a novel fouling-removal methodology for plate structure based on cavitation by multi-frequency ultrasonic guided waves is proposed, which can remove fouling on stainless steel plates. A numerical simulation method has been developed to study the acoustic pressure distribution on a steel plate. According to the simulation results, the distribution of sound pressure on the plate under triple-frequency excitation is denser and more prone to cavitation than in single-frequency cases and dual-frequency cases, which improves fouling removal rate. The stainless steel plate is immersed in water for the descaling experiment, and the results show that the fouling removal rates of three water-loaded stainless steel plates under different single-frequency excitation seem unsatisfactory. However, the multi-frequency excitation improves the descaling performance and the removal rate of fouling reaches 80%. This new method can be applied to the surface descaling of large equipment plates, which is of great significance for purifying water quality and protecting the ecological environment.